Reação de germoplasma de soja à Colletotrichum truncatum e Corynespora cassiicola - Furlani, Leonardo (2020)
Soybean culture in Brazil is attacked by several diseases that make it difficult to obtain high yields, especially anthracnose (Colletotrichum truncatum) and target spot (Corynespora cassiicola) because they are diseases with a complex and difficult to control pathosystem. In this way, the search for new control strategies becomes necessary, and in the present work, genetic management will be emphasized. The objective of this work was to evaluate the epidemiological parameters related to the sensitivity of 130 soybean cultivars (24 with adaptation for the Cerrado and 106 for the south of Brazil) to C. truncatum and C. cassiicola, and perform a cluster analysis, aiming to identify similar groups. As for the sensitivity assessments of C. truncatum, the objective was the development and validation of three diagrammatic scales aiming at assessing the severity of anthracnose in ribs, petioles and vegetables. The plants were grown in a protected environment, without the use of fungicides and inoculated with spores of C. truncatum and C. cassiicola. The studied parameters were latency period, disease severity, area under the anthracnose progress curve (AACPA) and target spot (AACPMA) and rate of progress. Severity assessments of C. truncatum followed the elaborated diagrammatic scales. The validation of the scales was performed by 8 evaluators who estimated the severities with and without the aid of the proposed scales, showing increases in the precision and accuracy of the evaluations, having shown adequacy and efficiency for the evaluation of the expression of anthracnose from soy. Using multivariate analysis for cultivar sensitivity experiments, they were grouped into 5 sensitivity groups by the K-means algorithm, for each disease and for each adaptation region. None of the cultivars studied showed complete resistance to C. truncatum and C. cassiicola, but there were variations in sensitivity between them, which have been verified since the beginning of the avaliations. The decision to choose cultivars is a strategy that can be considered for an adequate management of anthracnose and target spot in soybean culture, which associated with integrated management, can contribute to reduce the evolution of these diseases, which can affect the program of control, and in addition, this information can assist in genetic studies for breeders, collaborating for the identification of genotypes that can contribute to the improvement of soybean cultivars.